Assessing the detection zones of radar stations with the additional use of radiation from external sources - Ruban, Igor; Khudov, Hennadii; Lishchenko, Vitaliy; Pukhovyi, Oleksandr; Popov, Serhii; Kolos, Ruslan; Kravets, Taras; Shamrai, Nazar; Solomonenko, Yuriy; Yuzova, Iryna (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports the assessment of the detection zone of survey radar stations under a mode of single-place location. The detection zone under this mode significantly depends on the properties of the single-position effective surface of air objects scattering. The assessment of the detection zone of survey radar stations under a mode of the distributed location has been performed. It was established that the dimensions of the detection zone of air objects under a mode of the distributed location depend not only on the characteristics of the transmitting and receiving positions but on the system’s geometry and the information combining technique as well. It was established that the size and nature of the detection zones of air objects under a mode of distributed reception depend on the distance to the base line and the degree of suppression of the penetrating signal in the receiving position. The detection zone of survey radar stations was estimated when the modes of single-position and distributed location merge. It was established that the shape of an air object detection zone depends on the design features of a particular air object and would take a different form for different types of air objects. However, the general trend to increase the size of the detection zone and reduce the dependence of its shape on the foreshortening of an air object when the merged modes of single-position and distributed reception is inherent in all types of air objects. The quality of using the merging of single-position and distributed reception modes at the predefined flight altitude of an air object was assessed. It was established that the application of the non-coherent combination of the single-position and distributed processing channels would increase the size of the detection zone of stealth aircraft objects by at least 30 % compared to the size of the single-position radar detection zone